2020
DOI: 10.1080/23311886.2020.1778915
|View full text |Cite
|
Sign up to set email alerts
|

Exploring work environment factors influencing the application of teacher professional development in Ghanaian basic schools

Abstract: This study explored the work environment factors that support or constrain the application of teacher professional development initiatives in Ghanaian basic schools. Utilizing qualitative research paradigm, 15 teachers were purposively selected and interviewed from one educational district in Ghana. Findings from the study showed that headteachers support through the provision of the required teaching and learning resources, peer support through culture of shared norms, beliefs and values and the opportunity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Within the African context, there is paucity of literature on teacher CPD activities comparatively to pre-service teacher education. The available evidence suggests the predominance and participation in rarely organized CPD forms such as in-service training, workshops, and seminars (Abakah, 2019; Abonyi et al, 2020; Atta & Mensah, 2015; Oluremi, 2013). However, there is often the challenge of lack of school support for effective implementation of CPD activities, infrequent provision of CPD activities, lack of diversified practices, and teachers’ reluctance to engage in CPD activities (Geldenhuys & Oosthuizen, 2015).…”
Section: Conceptual Framework: Kennedy’s Model Of Cpd Practicesmentioning
confidence: 99%
“…Within the African context, there is paucity of literature on teacher CPD activities comparatively to pre-service teacher education. The available evidence suggests the predominance and participation in rarely organized CPD forms such as in-service training, workshops, and seminars (Abakah, 2019; Abonyi et al, 2020; Atta & Mensah, 2015; Oluremi, 2013). However, there is often the challenge of lack of school support for effective implementation of CPD activities, infrequent provision of CPD activities, lack of diversified practices, and teachers’ reluctance to engage in CPD activities (Geldenhuys & Oosthuizen, 2015).…”
Section: Conceptual Framework: Kennedy’s Model Of Cpd Practicesmentioning
confidence: 99%
“…The material dimension deals with resources and the physical environment that promote or demote teacher agency. Several researchers (Abonyi et al, 2020 ; Huang et al, 2021 ; Schwab et al, 2020 ; Toom et al, 2017 ) explored the effect of materials, resources, and physical environment on teachers’ agentic practices. Schwab et al’s ( 2020 ) study revealed that a higher perception of available resources results in the perception of inclusive teaching practices and satisfactory resources as a prerequisite for successful schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Huang et al ( 2021 ) suggested that available equipment and resources are connected with creative teaching. In addition, Abonyi et al ( 2020 ) found that the availability of required teaching and learning resources reinforced the transfer of teachers’ learning. Conversely, the lack of adequate teaching and learning materials inhibited the efficient transfer of teachers’ professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Also, on account that around 82% of the teachers in this study were aged between 20 and 39, they had quite a number of years of service. Hence, bespoke CPDs are imperative for their personal and professional growth (Desimone, 2009) instead of imported CPDs that may not take care of environmental factors affecting these teachers' professional development (Abonyi et al, 2020;Perry & Bevins, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the seeming importance of TCPD, Armah (2016, p.2) pointed out that the "disparity between the professional values and skills demanded from a 21st century teacher and those available among the teaching population" remain a key challenge to professional development efforts among Ghanaian teachers. Abonyi, Yeboah and Luguterah (2020) in their analysis of how environmental factors influence the application of teacher professional development in Ghanaian basic schools, also established that despite the significance of the type and availability of professional development programmes, headteachers' support through the provision of resources and peer support through the culture of shared values and norms are critical to individual teachers' ability to apply the knowledge acquired in their respective classroom. They further argued that rigid and inflexible teaching timetables and teacher workload were the main constraints that affect individual teacher's attendance in professional development programmes.…”
Section: Introductionmentioning
confidence: 99%